Strategi Komunikasi Pemasaran Viera Sutera dalam Mengenalkan Tenun Sutera Tradisional Garut - Santi Susanti; Wahyu Gunawan (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze the marketing communication strategy applied by Viera Sutera Garut in introducing traditional silk weaving products through social media, especially Instagram. The research used a descriptive qualitative approach with a single case study design, where data was collected through in-depth interviews, observation of social media activities, and visual documentation. The results show that Viera optimizes marketing communication through the consistency of visual content that highlights the beauty of distinctive motifs and colors, thus being able to build a strong brand aesthetic. Collaborations with designers have also expanded the reach of the audience and strengthened Viera's position as a premium wastra craftsman. The strategy of color differentiation and emphasis on the production process is used as a form of cultural storytelling that provides education to consumers. Instagram acts as a digital catalog that not only displays products, but also builds a professional identity and image as a culture-based MSME. The findings of this study are in line with the concept of integrated marketing communication, storytelling strategies, and niche market management as an effective approach in promoting local products. This study concludes that marketing communication does not only function as a promotional tool, but also as a means of cultural preservation and strengthening local identity through visual and collaborative narratives.